Comparative Innate and Adaptive Immune Responses in Atlantic Bottlenose Dolphins (Tursiops truncatus) With Viral, Bacterial, and Fungal Infections - Bossart, Gregory D.; Romano, Tracy A.; Peden-Adams, Margie M.; Schaefer, Adam M.; Rice, Charles D.; Fair, Patricia A.; Reif, John S. (Frontiers in Immunology, 2019)
Free-ranging Atlantic bottlenose dolphins (n =360) from two southeastern U.S. estuarine sites were given comprehensive health examinations between 2003 and 2015 as part of a multi-disciplinary research project focused on individual and population health. The study sites (and sample sizes) included the Indian River Lagoon (IRL), Florida, USA (n =246) and Charleston harbor and associated rivers (CHS), South Carolina, USA (n=114). Results of a suite of clinicoimmunopathologic tests revealed that both populations have a high prevalence of infectious and neoplastic disease and a variety of abnormalities of their innate and adaptive immune systems. Subclinical infections with cetacean morbillivirus and Chlamydiaceae were detected serologically. Clinical evidence of orogenital papillomatosis was supported by the detection of a new strain of dolphin papillomavirus and herpesvirus by molecular pathology. Dolphins with cutaneous lobomycosis/lacaziasis were subsequently shown to be infected with a novel, uncultivated strain of Paracoccidioides brasiliensis, now established as the etiologic agent of this enigmatic disease in dolphins. In this review, innate and adaptive immunologic responses are compared between healthy dolphins and those with clinical and/or immunopathologic evidence of infection with these specific viral, bacterial and fungal pathogens. A wide range of immunologic host responses was associated with each pathogen, reflecting the dynamic and complex interplay between the innate, humoral and cell-mediated immune systems in the dolphin. Collectively, these studies document the comparative innate and adaptive immune responses to various types of infectious diseases in free-ranging Atlantic bottlenose dolphins. Evaluation of the type, pattern and degree of immunologic response to these pathogens provides novel insight on disease immunopathogenesis in this species and as a comparative model. Importantly, the data suggest that in some cases infection may be associated with subclinical immunopathologic perturbations that could impact overall individual and population health.